Organizational Forms of Technical Impact Centralization - E. A. Reutsky (Наука и техника)
The paper considers one of the ways to improve further organization of maintenance and running repair of automobiles with the purpose to ensure their better serviceability and lower expenses on their operation.The main forms of transport facilities’ technical impact centralization have been described and analyzed in the paper. The paper provides a variety of schemes in structural and organizational forms of centralized production in connection with requirements in this or that basis.